Comprehensibility of Contraindications in German, UK and US Summaries of Product Characteristics/Prescribing Information-A Comparative Qualitative and Quantitative Analysis - Then, Melanie; Andrikyan, Wahram; Fromm, Martin; Maas, Renke (Journal of Clinical Medicine, 2022)
Contraindications (CIs) in Summaries of Product Characteristics (SmPCs)/Prescribing Information (PI) that lack clarity may pose a risk to medication safety and increase the risk for adverse drug reactions. We assessed and compared SmPCs/PI from three major drug markets regarding comprehensibility from the prescriber perspective, as well as usability in clinical decision support systems. 158 drugs met the following inclusion criteria: marketed in Germany (DE), United Kingdom (UK) and United States (US) and belonged to the 100 most recently FDA approved and/or 100 most frequently prescribed drugs in either country. In the 474 (3 x 158) SmPCs/PI all expressions for absolute CIs were identified, divided into 3999 stand-alone terms and evaluated according to 'clarity' and 'codability'. The average number of absolute CIs per drug differed drastically between the three markets (DE: 11.7, UK: 9.0, US: 4.6). Expressions were frequently unclear (DE: 27.2% (95% CI 25.2-29.2%), UK: 28.5% (26.2-30.9%), US: 22.6% (19.7-25.8%)). Moreover, 60.9% (58.6-63.1%), 63.6% (61.0-66.0%), and 64.7% (61.2-68.1%) of the expressions were not codable in DE, UK, and US, respectively. Taken together, in three major drug markets, statements regarding CIs in SmPCs/PI substantially differ in frequency and frequently lack clarity and codability which poses an unnecessary obstacle to medication safety.
CRIS-Team WoS Importer:2022-08-12